The Incidence of Labour-Service at Mari - Evans, D. Geoffrey
I. Work upon the Canals and Irrigation System II. Agricultural Corvées III. Conclusions IV. Periods of Labour-Service V. Royal Policies upon Labour-Service and Land Use.